Analysis of The Influence of Service Quality, Product Quality, Customer Value, and Brand Image On Customer Satisfaction at PT. Pegadaian (Persero) Banjarmasin Branch - Tusiana Dewi (PT. Hanken Sukses Jaya, 2023)
Research how the influence of service quality, product quality, customer value, and brand image on customer satisfaction at PT. Pegadaian (Persero) Banjarmasin Branch. 100 customers of PT. Pegadaian (Persero) Banjarmasin Branch was taken as a sample. As for the calculation results of the analysis of the description of the research variables with the SPSS (Statistical Package for Social Science) Version 23.0 program. The results of the study prove that service quality, product quality, customer value, and brand image have an effect on customer satisfaction at PT Pegadaian (Persero) Banjaramasin Branch.